Fractionalization and Entrepreneurial Activities - Sefa Awaworyi Churchill (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The vast majority of the literature on ethnicity and entrepreneurship focuses on the construct of ethnic entrepreneurship. However, very little is known about how ethnic heterogeneity affects entrepreneurship. This study attempts to fill the gap, and thus examines the effect of ethnic heterogeneity on entrepreneurial activities in a cross-section of 90 countries. Using indices of ethnic and linguistic fractionalization, we show that ethnic heterogeneity negatively influences entrepreneurship. We argue that potential channels that can explain the negative effect of fractionalization on entrepreneurship include trust, social network, social capital, innovation, and discrimination among others. Results are robust to several checks.
Keywords: 330; entrepreneurship; ethnic diversity; fractionalization